Transcriptome Profiling Identifies Candidate Genes Associated with the Accumulation of Distinct Sulfur γ-Glutamyl Dipeptides in Phaseolus vulgaris and Vigna mungo Seeds - Liao, Dengqun; Cram, Dustin; Sharpe, Andrew G.; Marsolais, Frédéric (Frontiers in Plant Science, 2013)
Common bean (Phaseolus vulgaris) and black gram (Vigna mungo) accumulate γ-glutamyl-S-methylcysteine and γ-glutamyl-methionine in seed, respectively. Transcripts were profiled by 454 pyrosequencing at a similar developmental stage coinciding with the beginning of the accumulation of these metabolites. Expressed sequence tags were assembled into Unigenes, which were assigned to specific genes in the early release chromosomal assembly of the P. vulgaris genome. Genes involved in multiple sulphur metabolic processes were expressed in both species. Expression of Sultr3 members was predominant in P. vulgaris, whereas expression of Sultr5 members predominated in V. mungo. Expression of the cytosolic SERAT1;1 and -1;2 was approximately four-fold higher in P. vulgaris while expression of the plastidic SERAT2;1 was two-fold higher in V. mungo. Among BSAS family members, BSAS4;1, encoding a cytosolic cysteine desulphydrase, and BSAS1;1, encoding a cytosolic O-acetylserine sulphydrylase were most highly expressed in both species. This was followed by BSAS3;1 encoding a plastidic β-cyanoalanine synthase which was more highly expressed by 10-fold in P. vulgaris. The data identify BSAS3;1 as a candidate enzyme for the biosynthesis of S-methyl-cysteine through the use of methanethiol as substrate instead of cyanide. Expression of GLC1 would provide a complete sequence leading to the biosynthesis of γ-glutamyl-S-methylcysteine in plastids. The detection of S-methylhomoglutathione in P. vulgaris suggested that homoglutathione synthetase may accept, to some extent, γ-glutamyl-S-methylcysteine as substrate, which might lead to the formation of S-methylated phytochelatins. In conclusion, 454 sequencing was effective at revealing differences in the expression of sulphur metabolic genes, providing information on candidate genes for the biosynthesis of distinct sulphur amino acid γ-glutamyl dipeptides between P. vulgaris and V. mungo.